Effect of Aegle marmelos methanolic extracts of leaf and fruit pulp on learning and memory in albino rats - Kumar, Pojala; K., Krishnakanth; Alla, Jagadeesh (International Journal of Basic & Clinical Pharmacology, 2020)
Background: The objective was to study the effect of Aegle marmelos methanolic extracts of leaf (LE) and fruit pulp extract (FE) on learning and memory in albino rats. 40 healthy wistar albino rats of either sex were randomly divided into 10 groups of 4 each (n=4), weighing about 150 to 200 gm were selected for the study. The extracts i.e. 1ml of 1% carboxy methyl cellulose, LE and FE at doses of 100 mg/kg and 200 mg/kg were administered per oral one hour before the experiment. Methods: Learning and memory was assessed by elevated plus maze and Hebb William maze. Latency time and number of entries were assessed by elevated plus maze whereas only latency was assessed by Hebb William maze. Results: Plant extracts of LE and FE at doses 100 mg/kg and 200 mg/kg have shown significant percentage reduction in latency time in elevated plus maze and Hebb William maze (p<0.05) and reduction in the number of entries in elevated plus maze. Conclusions: LE and FE at doses 200 mg/kg have shown significant effect on learning and memory.